Variation in soil enzyme activity with amendments of biochar and polyacrylamide in coal gangue soils - Qiuyun Fan; Na Li; Yuqing Geng; Ying Dong; ChaoYing Zhang (Scientific Reports)
Abstract Coal gangue is a prevalent solid waste material, and its utilization presents an urgent challenge. This study investigates the impact of incorporating biochar (BC) and polyacrylamide (PAM) into a composite matrix of coal gangue soil (CGS). We conducted incubation experiments to evaluate the physicochemical properties and enzyme activity of CGS with different ratios of BC (1%, 2%, and 5% designated as B1, B2, and B5) and PAM (0.02%, 0.05%, and 0.10% designated as P2, P5, and P10), compared to a control (CK) with no amendments. The results indicate that (1) the lowest bulk density was observed in the B5P10 treatment. The organic carbon content in B5P10 increased by 57.98% compared to the CK. (2) The activities of α-glucosidase, N-acetyl-glucosidase, and alkaline phosphatase in the B5P10 treatment increased by 112.34%, 110.77%, and 52.40%, respectively. The geometric mean values of enzyme activities showed no significant differences among the treatments B2P5, B2P10, B5P2, B5P5, and B5P10, but these were significantly higher than those in the CK. (3) The parameters of pH, active carbon, field capacity, and available phosphorus were identified as the main factors affecting enzyme activity. CGS incorporating 2% BC and 0.05% PAM is recommended for soil reconstruction in mining regions.